ICD-10-PCS extension with ICD-9 procedure codes to support integrated access to clinical legacy data. (February 2019) - Hernandez-Ibarburu, G.; Perez-Rey, D.; Alonso-Oset, E.; Alonso-Calvo, R.; Voets, D.; Mueller, C.; Claerhout, B.; Custodix, N.V.
Highlights: Methodology for the integration of ICD-9 procedures legacy data with ICD-10-PCS data. Extension of ICD-10-PCS with ICD-9 procedures concepts. Identification of incompatibilities between ICD-9 and ICD-10-PCS. Mapping rules from ICD-9 to ICD-10-PCS to increase the mapping reliability. Abstract: Since the creation of The International Classification of Diseases (ICD), new versions have been released to keep updated with the current medical knowledge. Migrations of Electronic Health Records (EHR) from ICD-9 to ICD-10-PCS as clinical procedure codification system, has been a significant challenge and involved large resources. In addition, it created new barriers for integrated access to legacy medical procedure data (frequently ICD-9 coded) with current data (frequently ICD-10-PCS coded). This work proposes a solution based on extending ICD-10-PCS with a subgroup of ICD-9-CM concepts to facilitate such integrated access. The General Equivalence Mappings (GEMs) has been used as foundation to set the terminology relations of these inserted concepts in ICD-10-PCS hierarchy, but due to the existence of 1-to-many mappings, advanced rules are required to seamlessly integrate both terminologies. With the generation of rules based on GEMs relationships, 2014 ICD-9 concepts were included within the ICD-10-PCS hierarchy. For the rest of the concepts, a new method is also proposed to increase 1-to-1 mappings. As results, with the suggested approach, the percentage of ICD-9-CM procedure concepts that can be mapped accurately (avoiding mappings to a large number of concepts) rise from 11.56% to 69.01% of ICD-9-Proc, through the extended ICD-10-PCS hierarchy.